Disagreement in expectations and the credibility of monetary authorities in the Brazilian inflation targeting regime - Luciano Vereda Oliveira; Alexandre Curi (EconomiA, 2016)
Based on market expectations reported by the Central Bank of Brazil for the SELIC interest rate, the IPCA inflation, the exchange rate (BRL/USD) and the growth rate of industrial production for four different forecasting horizons, this work analyzes the term structures of disagreement in expectations regarding the future values of these variables. It also investigates the driving factors of disagreement, paying special attention to the influence of monetary authorities' credibility. An extensive regression analysis shows that the levels of the term structures of disagreement are negatively related to the output gap (although this result is not very robust); and that the levels of the term structures of disagreement in expectations about the IPCA inflation rate and the SELIC interest rate have a strong negative relationship with central bankers' credibility; this relationship is positive in the case of the growth rate of industrial production. – – Com base nas expectativas de mercado divulgadas pelo Banco Central do Brasil para a taxa de juros (SELIC), a inflaç\~ao medida pelo IPCA, a taxa de câmbio (R/US) e a taxa de crescimento da produç\~ao industrial para quatro diferentes horizontes de previs\~ao, este trabalho analisa as estruturas a termo das divergências de expectativas quanto aos valores futuros dessas variáveis. Ele também investiga os fatores determinantes das divergências, em especial, a influência da credibilidade da autoridade monetária. Uma extensa análise de regress\~ao mostra que os níveis das estruturas a termo das divergências s\~ao negativamente relacionados com o hiato do produto (embora este resultado n\~ao é muito robusto); e que os níveis das estruturas a termo das divergências nas expectativas sobre a taxa de inflaç\~ao (IPCA) e a taxa de juros (SELIC) têm uma forte relaç\~ao negativa com a credibilidade do banco central; esta relaç\~ao é positiva no caso de a taxa de crescimento da produç\~ao industrial.
Keywords: 330; Disagreement in expectations; Monetary policy; Credibility; Term structures; Divergência de expectativas; Política monetária; Credibilidade; Estrutura a termo